The Olympic family? Young people, family practices and the London 2012 Olympic Games. Issue 2 (2nd April 2016) - Such, Elizabeth
ABSTRACT: The London Olympic and Paralympic Games in 2012 sought to 'Inspire a Generation' of young people to engage in sport. This article explores the ways in which a group of young people in the North West of England and the East of Scotland experienced the Games in the context of their everyday family and relational lives. Using a family practices theoretical framework and applying the concept of 'family ecocultural pathways', the article examines how watching the Olympics on television served as an opportunity for families to express their sport and physical activity values, needs and goals in their everyday practices of 'doing' and 'being' a family. Empirical data from the study is presented alongside critical explorations of the neoliberal policy and political context of the London 2012 Games. Discussion focusses on how sport legacy policy (and sport and physical activity policy in general) could be reconceptualised and reconstructed to include a family practices perspective.